Adsorption of arsenite and arsenate on binary and ternary magnetic nanocomposites with high iron oxide content - Ramos Guivar J.A. (2018)
Bare maghemite nanoparticles (Nps), binary, and ternary magnetic nanocomposites made with titanium dioxide (TiO2) and graphene oxide (GO) were synthesized by a facile and cheap coprecipitation chemical route, and used as magnetic nanoadsorbents to remove arsenite (As(III)) and arsenate (As(V)) from water. The structural, morphological, magnetic and surface properties were analyzed by XRD, TEM microscopy, FTIR and Raman vibrational spectroscopy, Mössbauer technique and N2 adsorption-desorption measurements. It was found that materials were composed of maghemite nanoparticles with crystallites diameters varying from 9 to 13 nm for bare Nps, binary and ternary nanocomposites, with these nanocomposites having a high percentage of maghemite phase (80%). The presence of TiO2 and GO in the binary and ternary materials was also confirmed. All the samples were found to show magnetic properties and a slight porosity, with a specific surface area that increases up to 82 m2 /g when the metal oxides Nps were supported on GO. The aqueous arsenic adsorption performance was studied from kinetic and equilibrium point of view, and the pH adsorption capacity dependence was evaluated aiming to explain the adsorption mechanism. The three nanocomposites prepared in this work exhibit high adsorption capacity for arsenic species, with values of maximum adsorption capacity ranging from 83.1 to 110.4 mg/g for As(III) and from 90.2 to 127.2 mg/g for As(V) from bare to ternary nanocomposites, and can be fast separated with a permanent magnet of neodymium (Nd) in less than 10 min. Therefore, these nanosystems can be proposed as good adsorbents for both arsenic species from water.